DECEPTIVE IS EFFECTIVE NEGOTIATION STRATEGIES TO CUSTOMERS FOR USING CONDOMS CONSISTENTLY - Putu Sukma Megaputri; Putu Kusuma Dewi Dian Prima; Cindy Meilinda Sari; I Dewa Ayu Rismayanti (INSIST, 2017)
The Consistency of condom use by the sex customers is very low. These problems occur due to the lack of negotiations carried out by the sex workers into their customers. This study aims to determine the most effective negotiation strategies for the customers to consistently using condoms. The study was conducted by using a survey cross-sectional of sex workers directly with the sample of 100 peoples, which who selected by a random cluster sampling in Denpasar city. The data collected by interviews conducted by using a questionnaire about the characteristics and modification Condom Influence Strategy Questionnaire (CISQ) developed by Noar. The results of the study show that about 63% of customers consistently used condoms in the past week. The effective negotiation strategies used so that customers consistently using condoms is deceptive by sex workers to their client's variables associated with consistent condom use is the availability of condoms and sex worker's age. Deceptive is the most effective strategy to increase consistent condom use.Keywords— Negotiations Condoms, Female Sex Workers, Consistency of Condom Use